(untitled) (Jurnal Ilmu Pendidikan dan Sains: Visioedusains, 2025)
This study aims to examine competition between plant species based on their density and distribution levels in three different habitat types: shaded habitats, transitional habitats, and habitats exposed to full light. The study was conducted on March 2, 2017 in the yard of the Department of Biology, Bogor Agricultural University. Data were collected using 1×1 m² quadrants, each divided into four parts for observation of species composition, density, distribution, and environmental parameters such as temperature, humidity, light intensity, pH, and soil temperature. The identification results showed that there were 14 weed species with significant variations in density and distribution in each habitat. Asystasia nemorum showed the highest density (33.7%) and was found in all quadrants, indicating high environmental tolerance and strong competitive ability through wide leaf morphology and deep fibrous roots. Clitoria ternatea was in second place (29.3%) with a creeping strategy to find optimal habitat. In contrast, species such as Cyperus rotundus and Spigelia anthelmia showed low density and distribution, despite having allelopathic potential. Environmental factors have been shown to play an important role in species competition, particularly light intensity and temperature which influence photosynthesis and root growth.